Optimalisasi Manajemen Komunitas melalui Sistem Informasi Terintegrasi Cloud Komunitas Pacitan Cerdas Kabupaten Pacitan - Roziqin, Mohamad Firzon Ainur; Qolbi, Muhammad Syifa'ul; Aruna, Alby; Iriaji, Iriaji; Surya, Eka Putri; Marcelliantika, Adinda; Wijaya, Ginanjar Atma (IAI Nasional Laa Roiba Bogor, 2024)
The optimization of community management through the Integrated Cloud Information System for the Pacitan Cerdas Community in Pacitan Regency aims to enhance the efficiency and effectiveness of data management and activity coordination. This program implements cloud technology to store, access, and manage community information in real-time and centrally. Methods include the development and implementation of a cloud-based information system, technical training for community members, and performance evaluation through usage data analysis. Results show significant improvements in data management, activity coordination, and member engagement. The implementation of this system is expected to support better sustainability and development of the community in Pacitan Regency.